Income Smoothing and Discretionary R&D Expenditures of Japanese Firms* - MANDE, VIVEK; FILE, RICHARD G.; KWAK, WIKIL (Contemporary Accounting Research, 2000)
Abstract During the recent recession (1991 to present), Japanese firms decreased their spending on R&D for the first time since World War II. The decreases have raised concerns that Japanese managers may be making suboptimal allocations to R&D. We test whether Japanese managers adjust R&D based on short‐term performance. Our results show that Japanese firms in several industries adjust their R&D budgets to smooth profits. Interestingly, adjustments to R&D are larger in expansion years. These results, similar to those documented with U.S. managers, point to myopic decision making by Japanese managers.